Effects of Cations and PH on Antimicrobial Activity of Thanatin and s-Thanatin Against Escherichia coli ATCC25922 and B. subtilis ATCC 21332 - Guoqiu Wu; Jiaxuan Ding; Hui Li; Linxian Li; Rui Zhao; Zilong Shen; Xiaobo Fan; Tao Xi (Current Microbiology, 2008)

Identification of genes transcribed by Haemophilus parasuis in necrotic porcine lung through the selective capture of transcribed sequences (SCOTS) - Hui Jin; Yun Wan; Rui Zhou; Liangjun Li; Rui Luo; Sihua Zhang; Junyong Hu; Paul R. Langford; Huanchun Chen (Environmental Microbiology, 2008)
Summary Haemophilus parasuis is the aetiological agent of Glässer's disease, which has received more attention in the past decade due to the increasing economic losses in the pig industry worldwide. Little is known about the mechanisms by which H. parasuis survives in the host. In this study, selective capture of transcribed sequences (SCOTS) was used to identify H. parasuis genes upregulated in necrotic porcine lung 7 days post infection. Thirty‐eight genes were identified that were upregulated during infection of the lung tissue of pigs, compared with growth in culture medium. In two examples chosen gene expression was not confined to the lungs, there being variation between tissues. The data support biofilm formation being an important mode of growth for colonization and/or persistence. Results from the in vitro studies suggest that, as for other pathogens, iron and oxygen restriction and heat stress are important environmental signals to regulate gene expression. This study has identified genes of H. parasuis that are upregulated during infection of porcine lung tissue as compared with in vitro growth conditions.

Enhancement of superoxide dismutase activity in the leaves of white clover (Trifolium repens L.) in response to polyethylene glycol-induced water stress - Wang Chang-Quan; Li Rui-Chang (Acta Physiologiae Plantarum, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Group Time Delay in the Reflection of P-Polarized Electromagnetic Plane Waves at a Stratigraphic Interface - Fu-Ping Liu; Rui-Zhong Li; Jin-yao Li; Hui-Guo Chen; Chang-Chun Yang (Mathematical Geosciences, 2008)

Simple sequence repeat analyses of interspecific hybrids and MAALs of Oryza officinalis and Oryza sativa - Gang Li; Wei Hu; Rui Qin; Huajun Jin; Guangxuan Tan; Lili Zhu; Guangcun He (Genetica, 2008)

Phylogenetic Analysis of Leymus (Poaceae: Triticeae) Inferred from Nuclear rDNA ITS Sequences - Li-na Sha; Rui-wu Yang; Xing Fan; Xiao-li Wang; Yong-hong Zhou (Biochemical Genetics, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Rapid Quantitative Detection of Vibrio parahaemolyticus in Seafood by MPN-PCR - Xiaoyan Luan; Jixiang Chen; Yu Liu; Yun Li; Juntao Jia; Rui Liu; Xiao-Hua Zhang (Current Microbiology, 2008)

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

Effects of RNA interference-induced tryptase down-regulation in P815 cells on IL-6 and TNF-α release of endothelial cells - Yi-feng Jiang; Feng-di Zhao; Xiao-bo Li; Yan-xia Ning; Xiu-ling Zhi; Rui-zhe Qian; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2008)

High level expression of a functional human/mouse chimeric anti-CD20 monoclonal antibody in milk of transgenic mice - Bo Tang; Shanshan Yu; Min Zheng; Fangrong Ding; Rui Zhao; Jianmin Zhao; Yunping Dai; Ning Li (Transgenic Research, 2008)

The research of air pollution based on spectral features in leaf surface of Ficus microcarpa in Guangzhou, China - Jie Wang; Ruisong Xu; Yueliang Ma; Li Miao; Rui Cai; Yu Chen (Environmental Monitoring and Assessment, 2008)

Cadmium Accumulation in the Edible Parts of Different Cultivars of Radish, Raphanus sativus L., and Carrot, Daucus carota var. sativa, Grown in a Cd-contaminated Soil - Rui-Lun Zheng; Hua-Fen Li; Rong-Feng Jiang; Fu-Suo Zhang (Bulletin of Environmental Contamination and Toxicology, 2008)

Molecular cloning and tissue specific expression of an elongation factor 1A gene in sugarcane stalks - Ai-Qin Wang; Ying-Zhi Qin; Xing-Zhi Ye; Ye-Geng Fan; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2008)

One of the possible mechanisms for the inhibition effect of Tb(III) on peroxidase activity in horseradish (Armoracia rusticana) treated with Tb(III) - Shaofen Guo; Rui Cao; Aihua Lu; Qing Zhou; Tianhong Lu; Xiaolan Ding; Chaojun Li; Xiaohua Huang (JBIC Journal of Biological Inorganic Chemistry, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Characterization of donor genome contents of backcross progenies detected by SSR markers in rice - Zhang-Ying Xi; Feng-Hua He; Rui-Zhen Zeng; Ze-Min Zhang; Xiao-Hua Ding; Wen-Tao Li; Gui-Quan Zhang (Euphytica, 2008)

Degradation of Hazardous Dyes in Wastewater using Nanometer Mixed Crystal TiO2 Powders under Visible Light Irradiation - Jun Wang; Ronghe Li; Zhaohong Zhang; Wei Sun; Xiaofang Wang; Rui Xu; Zhiqiang Xing; Xiangdong Zhang (Water, Air, & Soil Pollution, 2008)

Fusion insect-resistant gene mediated by matrix attachment region (MAR) sequence in transgenic sugarcane - Zhi-Nian Deng; Yuan-Wen Wei; Wei-Li Lü; Yang-Rui Li (Sugar Tech, 2008)

Changes of urban wetland landscape pattern and impacts of urbanization on wetland in Wuhan City - Xuelei Wang; Longmei Ning; Jing Yu; Rui Xiao; Tao Li (Chinese Geographical Science, 2008)

The glycosides from Lomatogonium rotatum - Yu-Lin Li; You-Rui Suo; Zhi-Xin Liao; Li-Sheng Ding (Natural Product Research, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Spatial distributions of organic carbon and nitrogen and their isotopic compositions in sediments of the Changjiang Estuary and its adjacent sea area - Jianhua Gao; Yaping Wang; Shaoming Pan; Rui Zhang; Jun Li; Fenglong Bai (Journal of Geographical Sciences, 2008)